Microstructural, Thermal, Crystallization, and Water Absorption Properties of Films Prepared from Never‐Dried and Freeze‐Dried Cellulose Nanocrystals. Issue 1 (23rd November 2020) - Hossain, Kazi M. Zakir; Calabrese, Vincenzo; da Silva, Marcelo A.; Schmitt, Julien; Bryant, Saffron J.; Islam, Md Towhidul; Felfel, Reda M.; Scott, Janet L.; Edler, Karen J.
Abstract: In this paper, the microstructural, optical, thermal, crystallization, and water absorption properties of films prepared from never‐dried (ND) and freeze‐dried (FD) cellulose nanocrystals (CNCs) are reported. Morphology of the ND CNCs reveals a needle‐like structure, while after freeze‐drying, they show a flake‐like morphology. Microstructural analysis of ND and FD CNCs are further studied via small angle X‐ray scattering to probe interactions. ND CNCs yield a transparent film with a low surface roughness (14 ± 4 nm), while the FD CNC film evidence a significant reduction of their transparency due to their higher surface roughness (134 ± 20 nm). Although Fourier transform infrared spectroscopy and energy‐dispersive X‐ray spectroscopy analyses reveal no chemical change occurs during the freeze‐drying process, yet a more intense thermal degradation profile is observed for FD CNC film, probably due to the higher oxygen ingress within the gaps created between the stacked flakes. This, in turn, results in a greater loss of crystallinity at a higher temperature (300 °C) compared to the ND CNC film. A rapid decrease in water contact angle of the FD CNC film proves that the morphology of flakes and their orientation within the film has a strong influence in increasing water absorption capacity. Abstract : Aggregation behavior of cellulose nanocrystals during film formation is reported in this study. Varying drying conditions can alter the microscopic structure, optical, thermal, crystallization, and water absorption properties of films without changing the chemical composition. The film properties influenced by their microstructures will provide fundamental guidance for the development of sustainable cellulose‐based films for diverse applications.